Systemic Mastocytosis With Features of Chronic Liver Disease, Proptosis and Itchy Hyper-Pigmented Skin Lesion - Md Benzamin, -; Islam, Md Rafiqul; Khadga, Mukesh; Begum, Fahmida; Mazumder, Wahiduzzaman; Thakur, Shashi Bhushan; Hasan, Md Mahmudul; Karim, ASM Bazlul (KYAMC Journal, 2020)
Mastocytosisis a rare disorder of functionally defective mast cells. Infiltration of this functionally defective mast cells and CD34+ mast cell precursors in various organ leads to clinical manifestation. Skin is the most common affected organ. In systemic mastocytosis along with skin, internal organs such as the liver, spleen, bone marrow, small intestines and eye also involve. Diagnosis is done on the basis of WHO diagnostic criteria. Here we presenting this rare entity presented to us with features of chronic liver disease, proptosis and itchy hyperpigmented skin lesion diagnosed as systemic mastocytosis. KYAMC Journal Vol. 11, No.-1, April 2020, Page 50-53